Normal inflammasome activation and low production of IL-23 by monocyte-derived macrophages from subjects with a history of reactive arthritis. (2013) - Välimäki, E; Aittomäki, S; Karenko, L; Kantonen, J; Pettersson, T; Turunen, U; Matikainen, S; Leirisalo-Repo, M; Repo, H
Abstract : Objectives: The pathogenesis of reactive arthritis (ReA) is incompletely understood but may involve aberration(s) in the host's innate immune response towards infecting microbes. We therefore studied the production of interleukin (IL)-1β, a marker of inflammasome activation, and of IL-6, IL-12, IL-23, and tumour necrosis factor (TNF)-α, promoters of T-cell differentiation, by peripheral blood mononuclear cells (PBMNs) and monocyte-derived macrophages from healthy subjects with a history of ReA. Method: The study included 10 human leucocyte antigen (HLA)-B27-positive healthy subjects with previous ReA triggered by Yersinia enterocolitica O:3 infection and 20 healthy reference subjects, of whom 10 were HLA-B27 positive. PBMNs and macrophages were cultured for 18 h with bacterial lipopolysaccharide (LPS), muramyl dipeptide (MDP), Yersinia, or their appropriate combinations. PBMNs were also stimulated with monosodium urate (MSU) crystals. Cytokine levels were measured using an enzyme-linked immunosorbent assay (ELISA) and the Luminex system. Results: IL-1β secretion was similar from cells of the ReA group and from the HLA-B27-positive and -negative reference groups. TNF-α production from macrophages upon co-stimulation of LPS and MDP increased in the order ReA group < HLA-B27-positive reference group < HLA-B27-negative reference group (p for a trend = 0.027). Similarly, Yersinia -induced TNF-α and IL-23 production increased in the same order (p for trend for TNF-α = 0.036; p for trend for IL-23 = 0.026). Conclusions: PBMNs and macrophages from healthy subjects with previous ReA show normal inflammasome activation and low TNF-α and IL-23 production. This low cytokine production may impair bacterial elimination and thereby contribute to the triggering of ReA.